2018
DOI: 10.24132/csrn.2018.2802.3
|View full text |Cite
|
Sign up to set email alerts
|

Using Images Rendered by PBRT to Train Faster R-CNN for UAV Detection

Abstract: Deep neural networks, such as Faster R-CNN, have been widely used in object detection. However, deep neural networks usually require a large-scale dataset to achieve desirable performance. For the specific application, UAV detection, training data is extremely limited in practice. Since annotating plenty of UAV images manually can be very resource intensive and time consuming, instead, we use PBRT to render a large number of photorealistic UAV images of high variation within a reasonable time. Using PBRT ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…To mitigate this situation, some authors made use of transfer learning rather than starting from scratch. Other research work such as [32] employed dedicated software to generate synthetic images to increase the number of samples in the dataset. Other techniques for enlarging the dataset that could be used in the future include data augmentation and the utilization of generative models such as generative adversarial network (GAN) for creating artificial data which are similar to the original real data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate this situation, some authors made use of transfer learning rather than starting from scratch. Other research work such as [32] employed dedicated software to generate synthetic images to increase the number of samples in the dataset. Other techniques for enlarging the dataset that could be used in the future include data augmentation and the utilization of generative models such as generative adversarial network (GAN) for creating artificial data which are similar to the original real data.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al in [32] addressed the issue of limited visual data for UAVs by creating their own artificial images. They used Physically Based Rendering Toolkit (PBRT) to generate photorealistic UAV images.…”
Section: A Visual Detection With Learned Featuresmentioning
confidence: 99%
“…It is done by overlaying 3d drone models on top of random backgrounds. Another method [17] improves on this by using a Physically Based Rendering Toolkit to render photorealistic images of drones.…”
Section: Introductionmentioning
confidence: 99%
“…Drone detection based on visual data (image or video) can be performed using handcrafted feature-based methods [ 8 , 21 , 22 ] and deep learning-based [ 6 , 23 , 24 , 25 ] algorithms. Handcrafted feature-based methods are based on traditional machine learning algorithms by using traditional descriptors such as scale-invariant feature transform (SIFT), histogram of oriented gradients (HOG), Haar, local binary pattern (LBP), deformable parts model (DPM), and generic Fourier descriptor (GFD) that provide low-level handcrafted features (edges, drops, blobs, and color information) and classical classifiers (support vector machine (SVM), AdaBoost)), whereas the second category relies on the learned features using two-stage (region-based convolutional neural network (R-CNN), Fast R-CNN, Faster R-CNN, and Mask R-CNN) and single-stage (single shot detector (SSD), RetinaNet, and you only look once (YOLO)) deep object detectors.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment results showed that, despite training in synthetic data, the proposed system worked well on realistic images of drones against a complex background. Peng et al [ 25 ] used the physical rendering instrumentation tool (PBRT) to solve the problem of limited visual data by creating photorealistic images of UAVs. The authors developed a large-scale training set of 60,480 rendered images, choosing different positions and orientations of UAVs, 3D models, external materials, internal and external camera characteristics, environmental maps, and the post-processing of rendered images.…”
Section: Introductionmentioning
confidence: 99%